OSCON Open Source Software Superstream Series Cloud Strategies and Implementation - Brazeal, Forrest; Simmons, Josh; Walker, John; Cockcroft, Adrian; Jodlowska, Ewa; Tsang, Ray; Roumeliotis, Rachel; Hightower, Kelsey (O'Reilly Media, Inc., 2020)
Watch the OSCON Live Coding-Go, Rust, and Python event here. This three-part series of half-day online events gives attendees an overarching perspective of software development from which to make decisions that strengthen and grow companies and industries, a deep knowledge of key open source technologies to make it happen, and a community in which both they and their companies can thrive. In part 2, Cloud Strategies and Implementation, we wanted to explore the cloud. In the blink of an eye, the cloud has become a pillar of software development. And big vendors, including Amazon, Microsoft, and Google, keep pushing the envelope, adding more and more services. Join us to learn how cloud strategies and their implementation can impact your business. This event is sponsored by Capital One and features spotlights on the Open Source Initiative and the Python Software Foundation. About the presenters: Rachel Roumeliotis is vice president of content strategy at O'Reilly, where she leads an editorial team that covers a wide variety of programming topics ranging from full stack to open source in the enterprise to emerging programming languages. She's been a programming chair for the O'Reilly OSCON, Fluent, Strata, Software Architecture, and Security Conferences. She's currently the programming chair for the OSCON and Strata Data & AI Superstream Series on O'Reilly online learning. She's been working in technical publishing for 10 years, acquiring content in many areas including mobile programming, UX, computer security, and AI. Kelsey Hightower has worn every hat possible throughout his career in tech and enjoys leadership roles focused on making things happen and shipping software. Kelsey is a strong open source advocate focused on building simple tools that make people smile. When he isn't slinging Go code, you can catch him giving technical workshops covering everything from programming to system administration. Forrest Brazeal is an enterprise cloud architect, speaker, and community advocate. Currently a senior manager at A Cloud Guru, he spent years designing applications for the cloud at Infor and Trek10. One of the original AWS Serverless Heroes, Forrest was also named one of Jefferson Frank's "Top 7 Global AWS Experts" in 2019. His first book, The Read-Aloud Cloud, is coming from Wiley in 2020. Josh Simmons is the president of the Open Source Initiative. John Mark Walker is the director of the Open Source Program Office at Capital One. Previo ...